THE PREVENTION OF CHILD OBESITY IN SCHOOLS: A PROPOSAL FOR INTERVENTION (Fiep Bulletin - online, 2013)
Current evidence suggests that numerous dietary and exercise-related initiatives aimed at preventing child obesity are not effective in preventing an increase in weight, but they can help to promote a healthy diet and higher level of physical activity. Being too overweight (obese) can cause health, psychological and social problems in children. Obese children are more likely to have weight and health problems when they are adults. Programmes designed to prevent obesity focus on modifying one or more factors that are considered to lead to this problem. This bibliographical review includes assessment studies of a variety of intervention programmes that featured an increase in physical activity and dietary changes, either alone or in combination. From the trials, there is no sufficient evidence to prove that any programme in particular can prevent child obesity, although exhaustive strategies aimed at fostering changes in diet and physical activity, together with psychosocial support and changes in the children's background context can help. There is a tendency for more recent initiatives to involve the local community and to include evaluations. Future research might regard changes in favour of the population as a whole as being useful, such as improvements in the type of available foods in schools and in the availability of safe places to run and play, and they should evaluate the effects on health and the costs over a period of several years.
Keywords: Child obesity; school intervention programmes; health